2011
DOI: 10.5860/crl-125rl
|View full text |Cite
|
Sign up to set email alerts
|

Google Scholar Users and User Behaviors: An Exploratory Study

Abstract: The University of Mississippi Library created a profile to provide linking from Google Scholar (GS) to library resources in 2005. Although Google Scholar does not provide usage statistics for institutions, use of Google Scholar is clearly evident in looking at library link resolver logs. The purpose of this project is to examine users of Google Scholar with existing data from interlibrary loan transactions and library Web site click-through logs and analytics. Questions about user status and discipline, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…However, criticisms of this tool include limited advanced search functionality, incomplete or inaccurate metadata, inflated citation counts, lack of usage statistics, and inconsistent coverage across disciplines. 8 There is also a lack of clarity regarding what GS actually indexes, and students are often unaware that GS's preferences must be manually set to link to libraries' resources. Because of this, students are often confused by the request to pay for articles or the need to click through to a library website.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, criticisms of this tool include limited advanced search functionality, incomplete or inaccurate metadata, inflated citation counts, lack of usage statistics, and inconsistent coverage across disciplines. 8 There is also a lack of clarity regarding what GS actually indexes, and students are often unaware that GS's preferences must be manually set to link to libraries' resources. Because of this, students are often confused by the request to pay for articles or the need to click through to a library website.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, despite the changing informational behaviour of both students and researchers, the use of Google is instrumental in accessing scholarly information. Herrera (2011) analysed the University of Mississippi's library logs, and revealed that the percentage of clicks originating from Google Scholar had grown from 4% in 2006 to 27% in 2009. This phenomenon is confirmed in Burns' doctoral thesis (2013), which demonstrated the predominance of the university when providing full text access to researchers using Google Scholar as their starting point in the search for scholarly information.…”
Section: Visibility Of the Repositories On The Web And In Google Searmentioning
confidence: 99%
“…It is difficult to determine GS market share because "GS usage information is not available to participating institutions or libraries" (Herrera, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%